Data Mining for Risks of Clozapine Side Effects, Including Neutropenia, Associated with Lithium Carbonate Administration: Analysis Using the Japanese Adverse Drug Event Report Database - Yuichi Uwai; Tomohiro Nabekura (Adis, Springer Healthcare, 2023)
Abstract Background and Objective Clozapine use is associated with development of neutropenia, and lithium carbonate may be co-administered to reduce this risk; however, this has not yet been adequately investigated. The present study examined whether lithium administration is associated with the risks of clozapine side effects, including neutropenia. Methods Data on patients taking clozapine, extracted from the Japanese Adverse Drug Event Report (JADER) database, were analyzed. Patients who developed clozapine side effects were identified by the Standardized Medical Dictionary for Regulatory Activities Queries. The relationship between the use of lithium and risk of clozapine side effects was examined using logistic regression analysis. Results The use of lithium was reported in 530 out of 2,453 clozapine users. Hematopoietic leukopenia, convulsion, and noninfectious myocarditis/pericarditis developed in 109, 87, and seven lithium-treated patients, and in 335, 173, and 62 untreated patients, respectively. Univariate analysis showed no relationship between lithium administration and the risks of hematopoietic leukopenia (adjusted odds ratio (aOR) 1.11; 95% confidence interval (CI) 0.98-1.25), and the association with the risks of convulsion (aOR 1.41; 95% CI 1.23-1.62) and noninfectious myocarditis/pericarditis (aOR 0.63; 95% CI 0.43-0.94). Multivariate analysis revealed that lithium use was independently associated with the risks of convulsion (aOR 1.40; 95% CI 1.21-1.60) and noninfectious myocarditis/pericarditis (aOR 0.62; 95% CI 0.41-0.91). Conclusion The risks of seizure and myocarditis, but not of neutropenia, in clozapine-treated patients may be altered by lithium. Although the JADER database is based on spontaneous reporting, the present results warrant further study.